Patterns of emergency admissions for ambulatory care sensitive conditions: a spatial cross-sectional analysis of observational data - Nigel Rice; Hugh Gravelle; Rita Santos (BMJ Open)
Objectives To examine the spatial and temporal patterns of English general practices’ emergency admissions for Ambulatory Care Sensitive Conditions (ACSCs).Design Observational study of practice level annual hospital emergency admissions data for ACSCs for all English practices from 2004-2017.Participants All patients with an emergency admission to a National Health Service hospital in England who were registered with an English general practice.Main outcome measure Practice level age and gender indirectly standardised ratios (ISARs) for emergency admissions for ACSC.Results In 2017, 41.8% of the total variation in ISARs across practices was between the 207 Clinical Commissioning Groups (CCGs) (the administrative unit for general practices) and 58.2% was across practices within CCGs. ACSC ISARs increased by 4.7% between 2004 and 2017, while those for conditions incentivised by the Quality and Outcomes Framework (QOF) fell by 20%. Practice ISARs are persistent: practices with high rates in 2004 also had high rates in 2017. Standardising by deprivation as well as age and gender reduced the coefficient of variation of practice ISARs in 2017 by 22%.Conclusions There is persistent spatial pattern of emergency admissions for ACSC across England both within and across CCGs. We illustrate the reduction in ACSCs emergency admissions across the study period for conditions incentivised by the QOF but find that this was not accompanied by a reduction in variation in these admissions across practices. The observed spatial pattern persists when admission rates are standardised by deprivation. The persistence of spatial clusters of high emergency admissions for ACSCs within and across CCG boundaries suggests that policies to reduce potentially unwarranted variation should be targeted at practice level.